Analisis Kemampuan Komunikasi Matematis Siswa pada Materi Lingkaran ditinjau dari Perbedaan Gender - Dewi, Sherli Pitrah; Maimunah, Maimunah; Roza, Yenita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to describe mathematical communication skills in the circle material in terms of students’ gender differences. This research method is a descriptive method with a qualitative approach. The subjects of this study were students of class VIII at MTsS Madinatun Najah Rengat, Indragiri Hulu Regency, Riau Province, totaling 16 students. The data collection instrument used in this study was a written test. While the data analysis technique used descriptive analysis. The results showed that the mathematical communication skills of female students on all indicators had higher scores than male students. Female students are categorized as good at solving mathematical problems so that they are able to communicate mathematical ideas using pictures or symbols and have better mathematical representations than male students. The mathematical communication ability of female students is higher than the mathematical communication ability of male students with the total average score for female students is 77.8% and the total average score for male students is 66.7% or a difference of 11, 1%.